Effective Phase‐Alignment for 2D Halide Perovskites Incorporating Symmetric Diammonium Ion for Photovoltaics. Issue 13 (24th May 2021) - Zhang, Yalan; Wen, Jialun; Xu, Zhuo; Liu, Dongle; Yang, Tinghuan; Niu, Tianqi; Luo, Tao; Lu, Jing; Fang, Junjie; Chang, Xiaoming; Jin, Shengye; Zhao, Kui; et al.
Abstract: New structural type of 2D AA′ n −1 M n X3 n +1 type halide perovskites stabilized by symmetric diammonium cations has attracted research attention recently due to the short interlayer distance and better charge‐transport for high‐performance solar cells (PSCs). However, the distribution control of quantum wells (QWs) and its influence on optoelectronic properties are largely underexplored. Here effective phase‐alignment is reported through dynamical control of film formation to improve charge transfer between quantum wells (QWs) for 2D perovskite (BDA)(MA) n ‐1 Pb n I3 n +1 (BDA = 1, 4‐butanediamine, 〈 n 〉 = 4) film. The in situ optical spectra reveal a significantly prolonged crystallization window during the perovskite deposition via additive strategy. It is found that finer thickness gradient by n values in the direction orthogonal to the substrate leads to more efficient charge transport between QWs and suppressed charge recombination in the additive‐treated film. As a result, a power conversion efficiency of 14.4% is achieved, which is not only 21% higher than the control one without additive treatment, but also one of the high efficiencies of the low‐ n ( n ≤ 4) AA′ n −1 M n X3 n +1 PSCs. Furthermore, the bare device retains 92% of its initial PCE without any encapsulation after ambient exposure for 1200 h. Abstract : The in situ optical spectra reveal a significantly prolonged crystallization window during the perovskite deposition via additive strategy. Finer thickness gradient by n values in the direction orthogonal to the substrate leads to more efficient charge transport between quantum wells and suppressed charge recombination in the additive‐treated film. Finally, the power conversion efficiency of 14.4% is obtained.